Analisis Cerpen "Tukang Cukur" Karya Budi Darma dengan Pendekatan Sosiologis Sastra - Resa Mai Linra; Abdurahman Abdurahman (Journal of Literature Review, 2026)
This analysis uses a sociological approach to literature to examine the short story Tukang Cukur. This short story tells the life of Gito, an elementary school child from a poor farming family in Getas Pejaten (Central Java) in the 1950s–1960s, who faces military violence and famine. The characters are positioned in the context of the conflict between communist and anti-communist ideologies. To interpret the text based on social theory, the method used in this analysis is a qualitative descriptive method. The results of the analysis are the themes of social class, state power, ideological propaganda, and the role of institutions (schools, the military) in the short story. Meanwhile, referring to theoretical analysis (Marxism, Bourdieu, Durkheim, feminism) shows the dominance of military symbolic capital and the marginalization of ordinary people. Suggestions for further research include comparative studies of literature with similar themes and studies of social acceptance in society.